2022
DOI: 10.1037/apl0000936
|View full text |Cite
|
Sign up to set email alerts
|

Gender, bottom-line mentality, and workplace mistreatment: The roles of gender norm violation and team gender composition.

Abstract: Although gender has been identified as an important antecedent in workplace mistreatment research, empirical research has shown mixed results. Drawing on role congruity theory, we propose an interactive effect of gender and bottom-line mentality on being the target of mistreatment. Across two field studies, our results showed that whereas women experienced more mistreatment when they had higher levels of bottom-line mentality, men experienced more mistreatment when they had lower levels of bottom-line mentalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Research has also positioned employee BLM as a moderator. Tai and colleagues (2021) examined the interactive effect of employee gender (male versus female) and employee BLM on the likelihood of the employee being mistreated. They found that women with high BLMs and men with low BLMs were more likely to be mistreated by their teams.…”
Section: A Review Of Core Research Findingsmentioning
confidence: 99%
“…Research has also positioned employee BLM as a moderator. Tai and colleagues (2021) examined the interactive effect of employee gender (male versus female) and employee BLM on the likelihood of the employee being mistreated. They found that women with high BLMs and men with low BLMs were more likely to be mistreated by their teams.…”
Section: A Review Of Core Research Findingsmentioning
confidence: 99%
“…Following Vaziri et al (2020) and Huang et al (2012), we omitted participants who failed one or more of the attentioncheck items. After matching the data for employees and their direct supervisors and accounting for missing data using listwise deletion (Lebel and Patil 2018;Tai et al 2022), we received 235 valid employee-supervisor dyad (78.3%) questionnaires. Of all employees, female and male respondents accounted for 72.3% and 27.7% of the sample, respectively.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…As Greenbaum et al (2012) developed the bottom-line mentality scale for both supervisors and subordinates, based on our research objective, we adopted the employee version of the bottom-line mentality scale. The four items were “I am solely concerned with meeting the bottom line,” “I only care about the business,” “I treat the bottom line as more important than anything else,” and “I care more about profits than employee well-being.” The same scale has also been used to measure the bottom-line mentality of employees by other studies (e.g., Eissa et al, 2020 ; Scrimpshire et al, 2021 ; Tai et al, 2021 ), providing further evidence for the validity of this scale. The Cronbach’s α of this scale was 0.85.…”
Section: Methodsmentioning
confidence: 73%
“…In addition to its direct influence, employee bottom-line mentality makes employees willing to undermine colleagues when they watch their supervisor undermines others ( Eissa et al, 2020 ). Moreover, Tai et al (2021) find that women with a bottom-line mentality received more mistreatment because those women are more likely to be perceived as violating gender norms.…”
Section: Hypothesis Developmentmentioning
confidence: 88%